Low loss composite nano ferrite with matching permittivity and permeability in UHF band. (April 2016) - Saini, Ashish; Rana, Kush; Thakur, Atul; Thakur, Preeti; Mattei, Jean Luc; Queffelec, Patrick
Graphical abstract: Highlights: Nano composites of hard and soft ferrite were synthesized. Sustained value of permittivity and permeability value are obtained up to mid UHF band. Ferromagnetic resonance extends above 1 GHz enabling high operational range of frequencies. Matching value of permittivity and permeability (both close to 4.6) obtained up to 600 MHz. Design shows better impedance matching and 55% area reduction. Abstract: Miniaturization of patch antenna using composite ferrite (Ni0.5 Zn0.3 Co0.2 Fe2 O4  + BaFe12 O19 ) is proposed in this paper. Substrate material was prepared using a wet chemical method and characterized for its structural and electromagnetic properties. Matching values of complex permittivity ( ε * = 4.5 + 0.1 j) and complex permeability ( μ * = 4.6 + 0.3 j) at 500 MHz were obtained from the electromagnetic characterization. Simulation result showed that matching and greater than unity value of both permittivity and permeability can reduce the size of antenna by almost 55%. Normalized characteristic impedance close to unity (∼1.022) was observed in the synthesized nano ferrite composites. This results in better impedance matching of the substrate with the surrounding space. Reflection loss was found to decrease (from −28 dB to −35 dB) and bandwidth increases (1.6–6%) over pure dielectric substrate. Therefore, composite ferrite is proposed as suitable candidate for effective miniaturization of antenna in microwave frequency range.